The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0084214
|View full text |Cite
|
Sign up to set email alerts
|

TRAF5 and TRAF3IP2 Gene Polymorphisms Are Associated with Behçet's Disease and Vogt-Koyanagi-Harada Syndrome: A Case-Control Study

Abstract: BackgroundTRAF5 and TRAF3IP2 have been reported to be associated with several autoimmune diseases. Behçet's disease (BD) and Vogt-Koyanagi-Harada (VKH) syndrome are two autoimmune uveitis entities whereby both genetic and environmental factors are thought to be involved.ObjectiveThe role of TRAF5 and TRAF3IP2 in BD and VKH has not yet been reported and was therefore the subject of this study.MethodsThe study included 789 BD patients, 940 VKH patients and 1601 healthy unrelated individuals. Genotyping was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…HaploView 4.2 was used to screen the candidate SNPs through a r 2 critical value of 0.8, as well as a minor allele frequency (MAF) larger than 0.05. Twenty-four SNPs from 19 genes were identified and included: one SNP (rs231775) of CTLA-4, 10 one SNP (rs2227981) of PDCD1, 11 one SNP (rs7574865) of STAT4, 12 one SNP (rs763780) of IL-17F, 13 one SNP (rs4754) of OPN, 14 one SNP (rs9494885) of TNFAIP3, three SNPs (rs310230, rs310236, rs310241) of JAK1, 16 one SNP (rs2301436) of FGFR1OP, 17 one SNP (rs755622) of MIF, 18 two SNPs (rs12569232, rs6540679) of TRAF5, 19 one SNP (rs13210247) of TRAF3IP2, 20 one SNP (rs17728338) of TNIP1, 20 one SNP (rs2488457) of PTPN22, 21 one SNP (rs76481776) of miR-182, 22 one SNP (rs3212227) of IL-12B, 23 two SNPs (rs442309, rs224058) of ADO-ZNF365-EGR2, 24 two SNPs (rs78377598, rs117633859) of IL23R-C1orf141, 24 one SNP (rs6498169) of CLEC16A, 25 and one SNP (rs4703863) of AGT10 (Table 1). 26 HLA typing was not performed in our SO patients.…”
Section: Snp Choice and Genotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…HaploView 4.2 was used to screen the candidate SNPs through a r 2 critical value of 0.8, as well as a minor allele frequency (MAF) larger than 0.05. Twenty-four SNPs from 19 genes were identified and included: one SNP (rs231775) of CTLA-4, 10 one SNP (rs2227981) of PDCD1, 11 one SNP (rs7574865) of STAT4, 12 one SNP (rs763780) of IL-17F, 13 one SNP (rs4754) of OPN, 14 one SNP (rs9494885) of TNFAIP3, three SNPs (rs310230, rs310236, rs310241) of JAK1, 16 one SNP (rs2301436) of FGFR1OP, 17 one SNP (rs755622) of MIF, 18 two SNPs (rs12569232, rs6540679) of TRAF5, 19 one SNP (rs13210247) of TRAF3IP2, 20 one SNP (rs17728338) of TNIP1, 20 one SNP (rs2488457) of PTPN22, 21 one SNP (rs76481776) of miR-182, 22 one SNP (rs3212227) of IL-12B, 23 two SNPs (rs442309, rs224058) of ADO-ZNF365-EGR2, 24 two SNPs (rs78377598, rs117633859) of IL23R-C1orf141, 24 one SNP (rs6498169) of CLEC16A, 25 and one SNP (rs4703863) of AGT10 (Table 1). 26 HLA typing was not performed in our SO patients.…”
Section: Snp Choice and Genotypesmentioning
confidence: 99%
“…1,9 In view of the similarities concerning the HLA disease association and the clinical similarities between SO and VKH, we decided to investigate whether associations found between VKH and a variety of non-HLA genes might also affect disease susceptibility for SO. Earlier reports describing a significant association between certain single nucleotide polymorphisms (SNPs) with VKH disease were identified and resulted in a total of 24 SNPs in 19 genes encoding for CTLA-4, 10 PDCD1, 11 STAT4, 12 IL-17F, 13 OPN, 14 TNFAIP3, 15 JAK1, 16 FGFR1OP, 17 MIF, 18 TRAF5, 19 TRAF3IP2, 19 TNIP1, 20 PTPN22, 21 miR-182, 22 IL-12B, 23 ADO-ZNF365-EGR2, 24 IL23R-C1orf141, 24 CLEC16A, 25 and AGT10. 26 Of these 24 SNPs, only an SNP located in PDCD1 was shown to be associated with SO, which confirms the hypothesis that both diseases, although sharing some features, are separate clinical entities mediated via different immunopathological pathways.…”
mentioning
confidence: 99%
“…93 The interaction of CD40 with CD40L is regulated by tumor necrosis factor receptorassociated factor (TRAF), and recent studies showed that three SNPs in TRAF5 including rs6540679, rs12569232, and rs10863888, and rs13210247 in TRAF3IP2 were associated with BD and VKH syndrome. 94 Additionally, increased expression of TRAF5 and increased production of TNF-α and IL-6 were found in individuals carrying the risk genotype of TRAF5 rs6540679. 94 Most recently, Hou et al 13 performed a GWAS in a group of 1538 VKH patients and 5603 unaffected individuals and found an association between non-HLA genes including IL-23R-C1ORF141 and ADO/ ZNF365/EGR2 with VKH syndrome.…”
Section: Genetic Advances On the Genes Involved In Th17 Cell Pathwaysmentioning
confidence: 99%
“…94 Additionally, increased expression of TRAF5 and increased production of TNF-α and IL-6 were found in individuals carrying the risk genotype of TRAF5 rs6540679. 94 Most recently, Hou et al 13 performed a GWAS in a group of 1538 VKH patients and 5603 unaffected individuals and found an association between non-HLA genes including IL-23R-C1ORF141 and ADO/ ZNF365/EGR2 with VKH syndrome. The five non-HLA genes were all found to be expressed in human iris tissue.…”
Section: Genetic Advances On the Genes Involved In Th17 Cell Pathwaysmentioning
confidence: 99%
“….Behçet's disease has been classified as an autoinflammatory disorder[25,26]. Two large genome-wide association studies (GWASs) reported the association between Behçet's disease and the single nucleotide polymorphism (SNP) of IL-10, IL-23R/ IL-12RB2, TRAF5, and TRAF3IP2 genes[27][28][29]. Pyoderma gangrenosum, characterized by sterile neutrophilic infiltration of the skin and other organs, is one of the clinical manifestations of a monogenic autoinflammatory disease, pyogenic arthritis, pyoderma gangrenosum, and cystic acne (PAPA) syndrome[22], in which CD2BP1 mutation results in the activation of the NLRP3 inflammasome[24].…”
mentioning
confidence: 99%